Wanting to be important with someone: Exploring the construction of close relationships, sexuality and 'intellectual disability' - Castell, Emily Louise (Curtin University, 2015)
Sexuality, relationships and ‘intellectual disability’ are constructed as fundamentally complex. Findings generated reflect causal layered analysis of twenty-six interviews with individuals labelled with ‘intellectual disability’ and reflections on interactions with the community. Assumptions on ‘intellectual disability’ and the systems surrounding so-labelled individuals compromise opportunities to engage in close relationships. The endurance of logical-positivism and individualism within dominant western culture is speculated to govern the ways sexuality, close relationships and ‘intellectual disability’ are understood and challenged.